Ramadhan di Jawa: Telaah Atas Karya Andree Mouller - Agus Purnomo (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2007)
This study aims to analyze the cultural representation of Ramadan in Java as described in the work of Andree Mouller. This study explores Mouller's perspective on the Ramadan tradition in Javanese society and how local elements interact with Islamic values in religious practices. The method used is library research with a descriptive-analytical approach. The main sources of research include the work of Andree Mouller, historical literature on Islam in Java, and research related to the culture of Ramadan in Indonesia. The results show that the Ramadan tradition in Java is the result of the acculturation of Islamic teachings and local culture, such as the rituals of megengan, padusan, and the distinctive tradition of breaking the fast together. Mouller's representation illustrates how Islamic values are combined with local wisdom, creating a unique Islamic identity. This study contributes to understanding the dynamics of Islam and culture in a historical context as well as in the study of religious anthropology.